If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 14 + x + 8 = 10 Reorder the terms: 14 + 8 + x + x = 10 Combine like terms: 14 + 8 = 22 22 + x + x = 10 Combine like terms: x + x = 2x 22 + 2x = 10 Solving 22 + 2x = 10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-22' to each side of the equation. 22 + -22 + 2x = 10 + -22 Combine like terms: 22 + -22 = 0 0 + 2x = 10 + -22 2x = 10 + -22 Combine like terms: 10 + -22 = -12 2x = -12 Divide each side by '2'. x = -6 Simplifying x = -6
| ex-2=12 | | 2(k-5)-7=1 | | g(p+3)=2x^2+2x+3 | | (4x-3)*(3x-2)= | | 14h-7h=-14 | | 3w+10+2w=5 | | -15/3=x | | -(b--4)=-13 | | 4x^2-21x+22=-4x+4 | | 3j-2j-1=11 | | 24x^2+6x-9=0 | | h(t)=-16t^2+79t+6 | | 42x-14=-17+17x | | 15x-7=5x-13 | | 3r-8=-8 | | v^2+7=0 | | 3x^2+10x+3=19-4x^2+16 | | 6x+2(6x+13)=188 | | 6y+16-2y=18 | | 18-2(8x-7)=22 | | 5t-1=-46 | | 6k+2=3k+5k | | 10x^2+10x+3=19-4x^2+16 | | X-5+2x-4=12 | | 6.09x^2+4.57x-8.86=0 | | (7x-3)(2x+9)=0 | | 7(-6+3z)=42 | | x^3=79 | | 5t^2-10t-50=0 | | 27c+5-25c=49 | | 9a+5a+7a+8a= | | 5(4x-2)=2(3+6x) |